Detecting Potential Dangers in Elderly Bathrooms using a PIR-Based Notification System and Magnetic Sensor - Dwi Arfi Ananda; Farid Akbar Siregar (Ilmu Bersama Center, 2025)
Bathrooms represent one of the most hazardous environments for elderly individuals due to the high risk of falls, prolonged inactivity, and delayed emergency response. Early detection of potentially dangerous situations is therefore crucial to improve safety and reduce injury risks. This study proposes a notification system for detecting potential dangers in elderly bathrooms using a Passive Infrared (PIR) sensor and a magnetic door sensor. The PIR sensor is utilized to monitor human presence and movement patterns, while the magnetic sensor detects door status to identify abnormal conditions, such as prolonged bathroom occupancy or lack of movement after entry. The system is designed to automatically trigger notifications to caregivers when predefined risk conditions are detected. The proposed system was implemented using a microcontroller-based platform and evaluated through a series of controlled experiments simulating typical and abnormal bathroom usage scenarios. Performance evaluation focused on detection accuracy, response time, and system reliability. The experimental results indicate that the system is capable of effectively identifying potentially dangerous situations and delivering timely alerts to caregivers. The integration of PIR and magnetic sensors provides a simple, low-cost, and non-intrusive solution for enhancing elderly safety in domestic environments. This research demonstrates the potential of sensor-based notification systems to support assisted living and improve the quality of care for elderly individuals.